THE NEXUS OF DIGITAL AND COGNITIVE SPACE: A SYSTEMATIC REVIEW OF AUGMENTED REALITY'S ROLE IN FOSTERING SPATIAL ABILITY IN MATHEMATICS EDUCATION - Wahid Mohamad; Prof. Dr. Sarson W DJ Pomalato., M.Pd; Prof. Dr. Nurhayati Abbas, M.Pd (RADJA PUBLIKA, 2026)
Spatial ability is a critical cognitive predictor of success in Science, Technology, Engineering, and Mathematics (STEM) fields, yet its development is often neglected in traditional mathematics curricula. This systematic literature review synthesizes and analyzes the empirical research on the use of Augmented Reality (AR) as a pedagogical intervention to enhance spatial ability in mathematics education. Following a rigorous search and screening protocol across the Dimensions, Scopus, and Semantic Scholar databases, this review examines the core findings from the resulting corpus of primary research articles. The analysis is structured around four key themes: the pedagogical approaches underpinning AR interventions, the influence of different AR technology modalities, the measured impact on learning outcomes, and the persistent challenges and future research directions. The findings reveal that AR is most effectively leveraged through constructivist, game-based, and collaborative learning frameworks, which transform abstract mathematical concepts into tangible, interactive experiences. The review delineates a